Acoustical measures in churches: Oporto's Clérigos church, a comprehensive example - António P. O. Carvalho (2000)
This paper summarizes the methodology applied on a research program in Church Acoustics. The acoustical behavior of Catholic churches must be analyzed regarding three domains: quality for speech (intelligibility), quality for music and quality of the sound distribution within the room. To characterize the physical response of each church several objective acoustical measurements (RT, EDT, etc.) are taken at several receiver locations and using two sound source positions (altar and nave) in each room. The quality of music and speech is judged subjectively by a group of listeners that is asked to evaluate live music performances and speech tests. The quality for music perception is judged using a seven-point semantic differential rating scale regarding several subjective parameters (intimacy, envelopment, etc.). The quality for speech perception is also measured objectively using the RASTI with and without the use of the churches' sound reinforcement systems from the altar area and from the elevated lateral pulpits. This paper presents the use of this methodology with the Porto's Clérigos church as a comprehensive example.